Nitrogen release from white clover (Trifolium repens L.) residue and ensuing plant–soil utilisation by arable rotations - Anderson, Fiona; Clough, Timothy; Andreucci, Mariana; Moot, Derrick (Frontiers in Agronomy, 2026)
White clover is grown in monoculture for seed production, and, after seed harvest, the crop residue decomposes and becomes a source of nitrogen (N) to the ensuing crop in the rotation. This research aimed to quantify the amount of N accumulated in white clover biomass during seed production, the time of N release from that residue, and its subsequent utilisation in the plant–soil system. Two field experiments were conducted in commercial white clover seed crops established via conventional cultivation (“Conventional”) or direct drill (“Direct Drill”) in Canterbury, New Zealand. After seed harvest, the Conventional clover was replaced with a kale seed crop, whereas the Direct Drill clover was taken for a second season of seed production. For 238 days after seed harvest, the amount of N was measured in white clover residue, ensuing crop biomass and soil mineral N (NH4+, NO3−) in 0–10-, 10–20-, and 20–40-cm depths. Fallow subplots were created to enable estimation of the effect of N uptake by the ensuing crop. Soil N mineralisation was estimated using the acetylene (C2H2) reduction assay method. Total soil N (%) was determined at 0 and 238 days after seed harvest. Residue N content decreased in an asymptotic manner, over thermal time, with readily decomposable components (lamina, petiole, and floret) mineralised first. Residue-N had been 70% mineralised 760°Cd after harvest and was 95% decomposed after 1,600°Cd. Under the ensuing crop, total soil N increased by 226–232-kg N/ha, which was consistent with the quantity of N supplied as clover residue. In fallow plots, the total soil N increase was ~50% less than the increase under actively growing plants. It was estimated that unaccounted-for N had leached below the 40-cm depth. Ensuing crop N uptake was of comparable magnitude to the N available in both experiments. It was estimated that, due to N inputs, N from clover residue would be mineralised in the spring following seed harvest. This research concluded that the white clover seed crop residue rapidly released N, which was estimated to not be at risk of loss to the environment, provided the crop rotation proceeded without an extended fallow period.